Linking leaders’ personality, leadership style and employee engagement : evidence from SMES at Kuantan, Malaysia - Li, Feng (2018)
Nowadays, leaders and subordinates are key issues in building and sustaining business operations especially in the Small and Medium Sized Enterprises (SMEs). However, it is commonly found that their employees are disengaged as the turnover rate keeps on increasing. The potential reasons are the ineffective leadership styles which is related to leader’s personality. Hence, this research was conducted to identify the relationship between the leaders’ personalities, leadership styles and employee engagement in SMEs specifically at Kuantan Pahang Malaysia. There are five personality studies in this research which are Openness, Conscientiousness, Extraversion, Agreeableness and Neuroticism; three types of leadership style were adopted, namely Task-Oriented, Relations-Oriented and Change-Oriented. Meanwhile, it also covers three elements of employee engagement which are vigor, absorption and dedication. Two sets of questionnaires were developed and distributed to the managers and their subordinates respectively. A total of 160 leaders and 320 subordinates participated in this study. The statistic results showed that Conscientiousness trait and Task-oriented leadership styles are most popular among the surveyed leaders. Openness, Conscientiousness, Extraversion and Neuroticism are positively related with Task-Oriented, Relations-Oriented and Change-Oriented leadership. Meanwhile, Extraversion is the most contributor to Task-Oriented Leadership Style and only Agreeableness is negatively related to Task-Oriented and Relations-Oriented leadership Style. Furthermore, five personalities and three types of leadership styles are positively correlated with employee engagement. Only Extraversion and Conscientiousness are contributor to employee engagement and Extraversion is more than Conscientious. Hence, organizations can use the personality test to recruit or promote the preferred leaders either in the aspect of leader’s personality or leadership style, to enhance the effectiveness of employee engagement towards achieving organizational competitiveness.